2007
DOI: 10.1007/s11096-007-9176-1
|View full text |Cite
|
Sign up to set email alerts
|

Hospital morphine preparation for abstinence syndrome in newborns exposed to buprenorphine or methadone

Abstract: This hospital morphine solution is adequate for management of NAS. Preparations showed good stability and doses could be adjusted with a margin of 0.02 mg. The onset of NAS occurred within 24 h after birth in methadone-exposed infants (range 6-24 h) and within 48 h after birth in buprenorphine-exposed infants (range 24-168 h). Due to the possibility of delayed onset of NAS up to 7 days, infants born to mothers treated with buprenorphine should be kept in the hospital for an appropriate surveillance period. Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 28 publications
3
35
0
Order By: Relevance
“…Of 1111 citations identified, 140 full‐text papers were assessed for eligibility, and 18 studies 18, 19, 20, 21, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49 (reported in 23 papers 18, 19, 20, 21, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52) satisfied our inclusion criteria (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of 1111 citations identified, 140 full‐text papers were assessed for eligibility, and 18 studies 18, 19, 20, 21, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49 (reported in 23 papers 18, 19, 20, 21, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52) satisfied our inclusion criteria (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The only three RCTs 19, 20, 21 (six papers 19, 20, 21, 50, 51, 52) that have been conducted to date were included (223 participants; published 2005–10) (Supporting information, Table S2). Fifteen OBSs 18, 34, 35, 36, 37, 38, 39, 41, 42, 43, 44, 45, 46, 47, 48 (17 papers) 18, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49 enrolled a total of 1923 participants in prospective 18, 34, 35, 36, 37, 38, 39, 41, 42, 45, 46, 47 ( n  = 12) or retrospective 43, 44, 48 ( n  = 3) cohort studies published 2001–15. No case–control studies were identified.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations